2017
DOI: 10.1021/acs.orglett.7b02922
|View full text |Cite
|
Sign up to set email alerts
|

Intermolecular Amidation of Quinoline N-Oxides with Arylsulfonamides under Metal-Free Conditions

Abstract: An efficient method for the synthesis of N-(quinolin-2-yl)sulfonamides is described. The intermolecular amidation of quinoline N-oxides with sulfonamides proceeded smoothly in the presence of PhI(OAc) and PPh to afford N-(quinolin-2-yl)sulfonamides in satisfactory to excellent yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 20 publications
0
19
0
Order By: Relevance
“…Bao's group developed a new method to synthesize quinoline sulfonamides 111 from quinoline N-oxides, sulfonamides, PhI(OAc) 2 , and PPh 3 (Scheme 32). [54] The method is applicable to a variety of quinoline N-oxides and sulfonamides. Sulfonamides react with PhI(OAc) 2 to produce sulfonyl imino iodo arene 112 and acetic Ni-catalyzed sulfonamidation using N-fluorobenzenesulfonimide (NFSI, 115) as the amidating reagent was an efficient method described by Wu's group in 2019 (Scheme 33).…”
Section: Sulfoximination and Sulfonamidationmentioning
confidence: 99%
“…Bao's group developed a new method to synthesize quinoline sulfonamides 111 from quinoline N-oxides, sulfonamides, PhI(OAc) 2 , and PPh 3 (Scheme 32). [54] The method is applicable to a variety of quinoline N-oxides and sulfonamides. Sulfonamides react with PhI(OAc) 2 to produce sulfonyl imino iodo arene 112 and acetic Ni-catalyzed sulfonamidation using N-fluorobenzenesulfonimide (NFSI, 115) as the amidating reagent was an efficient method described by Wu's group in 2019 (Scheme 33).…”
Section: Sulfoximination and Sulfonamidationmentioning
confidence: 99%
“…Amidation of quinoline N ‐oxides with sulfonamides has been found to proceed in the presence of PhI(OAc) 2 and PPh 3 through 1,3‐dipolar [3+3]‐cycloaddition as shown on Scheme 26. [ 50 ]…”
Section: Deoxygenative C–h Functionalizationmentioning
confidence: 99%
“…doi.org/10.1002/ejoc.202001115 Amidation of quinoline N-oxides with sulfonamides has been found to proceed in the presence of PhI(OAc) 2 and PPh 3 through 1,3-dipolar [3+3]-cycloaddition as shown on Scheme 26. [50] Scheme 26. Deoxygenative amidation of quinoline N-oxides with arylsulfonamides and proposed mechanism.…”
Section: Deoxygenative Aminationmentioning
confidence: 99%
“…Iodine reagent as an eco-friendly and inexpensive reagent could induce functional groups to the 2-position of quinoline Noxides derivatives. [15] In 2017, Yu and colleagues reported that quinoline N-oxides and sulfonamides were induced by PhI(OAc) 2 (PIDA) and PPh 3 to synthesize 2-sulfonamideyl quinoline. Nevertheless, a stoichiometric amount of phosphorus reagent was necessary for the successful intermolecular sulfamidation.…”
Section: Introductionmentioning
confidence: 99%
“…In 2017, Yu and colleagues reported that quinoline N ‐oxides and sulfonamides were induced by PhI(OAc) 2 (PIDA) and PPh 3 to synthesize 2‐sulfonamideyl quinoline. Nevertheless, a stoichiometric amount of phosphorus reagent was necessary for the successful intermolecular sulfamidation . In addition, PhI(OAc) 2 has become one of the most popular research topics in organic synthesis.…”
Section: Introductionmentioning
confidence: 99%